Anisotropy in tactile time perception. (July 2020) - Hidaka, Souta; Tamè, Luigi; Zafarana, Antonio; Longo, Matthew R.
Abstract: Spatial distortions in touch have been investigated since the 19th century. For example, two touches applied to the hand dorsum feel farther apart when aligned with the mediolateral axis (i.e., across the hand) than when aligned with the proximodistal axis (along the hand). Stimulations to our sensory receptors are usually dynamic, where spatial and temporal inputs closely interact to establish our percept. For example, physically bigger tactile stimuli are judged to last longer than smaller stimuli. Given such links between space and time in touch, we investigated whether there is a tactile anisotropy in temporal perception analogous to the anisotropy described above. In this case, the perceived duration between the onset of two touches should be larger when they are aligned with the mediolateral than with the proximodistal axis of the hand dorsum. To test this hypothesis, we asked participants to judge which of two tactile temporal sequences, having the same spatial separation along and across the dorsum, felt longer. A clear anisotropy of the temporal perception was observed: temporal intervals across the hand were perceived as longer than those along the hand. Consistent with the spatial anisotropy, the temporal anisotropy did not appear on the palm side of the hand, indicating that the temporal anisotropy was based on perceptual processes rather than top-down modulations such as attentional or decisional/response biases. Contrary to our predictions, however, we found no correlation between the magnitudes of the temporal and spatial anisotropies. Our results demonstrated a novel type of temporal illusion in touch, which is strikingly similar in nature to the previously reported spatial anisotropy. Thus, qualitatively similar distorted somatosensory representations appear to underlie both temporal and spatial processing of touch.